Africanisation and Community-Based Water Resource Governance. Issue 2 (3rd July 2022) - Shoko, Evans; Naidu, Maheshvari
Abstract: To optimise water as a "vehicle" for development, strategies are necessary that are appropriate in a situated African setting. On the one hand, many African scholars advocate public governance that is rooted in African philosophy and culture. This type of governance is viewed as potentially capable of employing indigenous knowledge systems that are familiar to African people and local communities. On the other hand, some scholars posit that Africanisation should not be a total rejection of certain progressive western concepts. This article, in turn, attempts to demonstrate the importance of community-based water resource governance as a resource for Africanisation and the basis for community development, while acknowledging the challenges to the realisation of this goal. Using rhizomatic discourse analysis, the article connects seemingly diverse arguments to suggest the efficacy of Africanising water resource governance. Citing several examples from the African continent, the article argues for using locally available indigenous and scientific methods of water use and distribution. The article provides a rationale for using storytelling to shape the narratives and actions that enable communities to solve their water conflicts or challenges. The article concludes that while localising water governance and peacebuilding is key, due to technological advances it is practical to merge some western methods of water governance with locally based initiatives.